Glandular Cystitis. Case presentation - Nelson Cuéllar Suárez; Ives de la Caridad Otero Pérez; Heydisandy Peña Martín (Medisur)
Glandular Cistitis is an infrequent proliferative lesion, it is composed of glandular structures , columnar and mucin-secreting intestinal cells.. It is located inside the bladder mucosa and submucosa. It has been found in patients of all ages, including children. To present the clinical and anatomopathological characteristics of a rare disease and the interest that it may have for in training residents, it was decided to present the case of a 21 year old black male patient, with a history of dysuria, Increased urinary frequency in the day, night and urgency, as well as repeated episodes of macroscopic hematuria, with clinical diagnosis of glandular cystitis confirmed by biopsy.